ON ELECTRONIC TESTING KNOWLEDGE IN PHYSICS - SMETANOVÁ, Dana (Trends in education, 2015)
The paper deals with electronic multiple choice tests. We discuss limiting the probability of accidental tip. The advantages and disadvantages of these tests are discussed with respect to the physical science. Physics has some specifics which are presented and which must be take into consideration during the testing of students.
Keywords: physics; multiple choice tests; creation of the examples.